SOSIALISASI PERAN MASYARAKAT DALAM PENGAWASAN DAN PENGGUNAAN DANA DESA: DI DESA GOLO KANTAR, KECAMATAN BORONG, KABUPATEN MANGGARAI TIMUR - alupan, Anto; Pena, Veronika Ruba; Budiman, Oktavianus (Jurnal Pengabdian Multidisiplin Indonesia (JUPEMI), 2025)
Community oversight and participation in the management of Village Funds play a crucial role in realizing transparent, accountable, and participatory village financial governance. However, the lack of public understanding regarding regulations and monitoring mechanisms has led to limited community involvement. This community service program aims to enhance the understanding of the people of Golo Kantar Village, Borong Sub-district, East Manggarai Regency, through the dissemination of information on the community’s role in the utilization of Village Funds. The community service methods include lectures, interactive discussions, and monitoring simulations of Village Funds. The results of the program indicate an increase in community knowledge regarding their rights to oversight, reporting mechanisms, and strategies to promote transparency. This initiative is expected to serve as a starting point for strengthening the community’s capacity to actively engage in the planning, implementation, and supervision of Village Funds.